INFLUENCE of THE EVAPORATOR POSITION IN STATIC DOMESTIC REFRIGERATORS - Kinoshita, D. [UNESP]; Gasche, J. L. [UNESP] (Int Inst Refrigeration, 2011)
The temperature and velocity distributions of the air inside the cabinet of domestic refrigerators affect the quality of food products. If the consumer knows the location of warm and cold zones in the refrigerator, the products can be placed in the right zone. In addition, the knowledge of the thickness of thermal and hydrodynamic boundary layers near the evaporator and the other walls is also important. If the product is too close to the evaporator wall, freezing can occur, and if it is too close to warm walls, the products can be deteriorated. The aim of the present work is to develop a steady state computational fluid dynamics (CFD) model for domestic refrigerators working on natural convection regime. The Finite Volume Methodology is chosen as numerical procedure for discretizing the governing equations. The SIMPLE-Semi-Implicit Method for Pressure-Linked Equations algorithm applied to a staggered mesh was used for solving the pressure-velocity coupling problem. The Power-Law scheme is employed as interpolation function for the convective-diffusive terms, and the TDMA-Tri-Diagonal Matrix Algorithm is used to solve the systems of algebraic equations. The model is applied to a commercial static refrigerator, where the cabinet is considered an empty three-dimensional rectangular cavity with one drawer at the bottom of the cabinet, but without shelves. In order to analyze the velocity and temperature fields of the air flow inside the cabinet the evaporator temperature, Te, was varied from -20 degrees C to 0 degrees C, and nine different evaporator positions are evaluated for evaporator temperature of -15 degrees C. The cooling capacity of the evaporator for the steady state regime is also computed for each case. One can conclude that the vertical positioning of the evaporator inside the cabinet plays an important role on the temperature distribution inside the cabinet.